A review of how to do an acyclic diene metathesis reaction. Issue 1 (19th July 2016) - Li, Hong; Caire da Silva, Lucas; Schulz, Michael D; Rojas, Giovanni; Wagener, Kenneth B
Abstract: Recent reviews have described many advances made previously in acyclic diene metathesis (ADMET) polymerization. This mini‐review emphasizes the experimental considerations for successful ADMET reactions. Several factors that are important in ADMET polymerization are discussed, following a description of the discovery and the polycondensation nature of ADMET chemistry. Typical experimental techniques including bulk and solution ADMET polymerizations commonly used to obtain high‐molecular‐weight polymers are also reviewed. © 2016 Society of Chemical Industry Abstract : This review describes the various factors that contribute to successful ADMET polymerization from an experimental point of view.